Učinkovitost pojmovne mape pred branjem in po njem v 3. razredu osnovne šole - Ropič, Marija (Revija za elementarno izobraževanje, 2011)
The Effectiveness of Concept Mapping for Pre-Reading Activities and After-Reading Activities in the 3rd Grade of Primary School. If we know how to read, it does not mean that we also understand the text. For this we need much more than simply decoding letters, words and word groups. An awareness that reading is still the most effective means for acquiring knowledge, directs teachers to develop reading skills so that the reader spends less energy and time extracting the required information from a text. For this purpose we use different types of effective strategies for different parts of the learning process and complex reading strategies covering the entire learning process. A reader’s prior knowledge and their vocabulary influence their comprehension. A concept map is a method of activating prior knowledge. The general process introduces brainstorming, where we make associations. We categorize these associations in conceptions of a hierarchical structure from superior to lower. The special graphic structure facilitates the remembering of concepts and making connections with previous knowledge. Concept mapping has an impact on memorizing new words. Using this method, we performed a five-month study in the grade 3 of primary schools (age 8) and examined the effectiveness of concept mapping in pre-reading activities (the number and manner of written associations) and in after reading activities (written information obtained by reading).
Keywords: concept mapping; association; categorization of concepts; prior knowledge; vocabulary; pre-reading activity; after-reading activity